PENGARUH KEPEMILIKAN SAHAM DAN KINERJA KEUANGAN TERHADAP PENGUNGKAPAN INTERNET FINANCIAL REPORTING (IFR) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013) - M. Riduan Abdillah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This research aimed to analyze the effect of stock ownership proxy for managerial ownership and possession blockholder and financial performance on the disclosure of Internet Financial Reporting (IFR). The population in this research are all companies listed on the Indonesia Stock Exchange in 2013. Based on the purposive sampling method, the number of samples in this research as many as 102 companies. Research hypothesis testing using multiple regression analysis via SMART PLS 2.0 M3. Results of hypothesis testing found that managerial ownership and possession blokholder significant positive effect on the disclosure of Internet Financial Reporting (IFR). Financial performance has no significant effect on the disclosure of Internet Financial Reporting (IFR).